Pathological complete response in invasive breast cancer treated by skin sparing mastectomy and immediate reconstruction following neoadjuvant chemotherapy and radiation therapy: Comparison between immunohistochemical subtypes. (April 2017) - Barrou, J.; Bannier, M.; Cohen, M.; Lambaudie, E.; Gonçalves, A.; Bertrand, P.; Buttarelli, M.; Opinel, P.; Sterkers, N.; Tallet, A.; Zinzindohoué, C.; Houvenaeghel, G.
Abstract: Context: Even if neoadjuvant chemotherapy (NACT) and oncoplastic techniques have increased the breast conserving surgery rate, mastectomy is still a standard for multifocal or extensive breast cancers (BC). In the prospect of increasing breast reconstruction, an alternative therapeutic protocol was developed combining NACT with neoadjuvant radiation therapy (NART), followed by mastectomy with immediate breast reconstruction (IBR). The oncological safety of this therapeutic plan still needs further exploration. We assessed pathological complete response (pCR) as a surrogate endpoint for disease free survival. Methods: Between 2010 and 2016, 103 patients undergoing mastectomy after NACT and NART were recruited. After CT and RT were administrated, a completion mastectomy with IBR by latissimus dorsi flap was achieved 6 to 8 weeks later. pCR was defined by the absence of residual invasive disease in both nodes and breast. Histologic response was analyzed for each immunohistochemical subset. Results: pCR was obtained for 53.4% of the patients. This pCR rate was higher in hormonal receptor negative (HER2 and triple negative) patients when compared to luminal tumours (69.7% vs 45.7%, p=0.023). Discussion: The pCR rate found in this study is higher than those published in studies analyzing NACT (12.5%-27.1%). This can be explained by the combination of anthracycline and taxane, the use of trastuzumab when HER2 was overexpressed but also by RT associated to NACT. Conclusion: Inverting the sequence protocol for BC, requiring both CT and RT, allows more IBR without diminishing pCR and should therefore be considered as an acceptable therapeutic option. Highlights: Neoadjuvant sequential association of chemo-radiotherapy allows SSM with IBR. pCR after neoadjuvant chemotherapy and radiation therapy reaches 53.4%. HoR negative are more sensitive than luminal tumors (pCR = 69.7% vs 45.7%, p = 0, 023). Completion SSM-IBR is a safe procedure with a low complication rate (9.7%).